Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.1002/qua.27062
|View full text |Cite
|
Sign up to set email alerts
|

Capturing experimental properties in computationally efficient faceted titania nanoparticle models

Abstract: Understanding the surface chemistry of nanostructured TiO2 has long been a priority to improve photochemical device efficiency. Faceted nanoparticles, characterized by known facets not at thermodynamically ideal ratios, are particularly challenging to model due to the large number of chemical and computational parameters that must be chosen for which there is no experimental guidance. This research supplies a modeling framework for faceted TiO2 nanoparticles that provides rationale for such decisions. By perfo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 60 publications
0
2
0
Order By: Relevance
“…These “rattled” structures allowed the optimizer to escape local minima and relax to a lower energy ground state structure. Such symmetry breaking has been shown to improve the optimization behavior in TiO 2 nanoparticles previously . As a general rule of thumb, it was suggested that structural perturbations of around −40% to +20% to provide optimal results …”
Section: Designing Robust Computational Modelsmentioning
confidence: 97%
See 1 more Smart Citation
“…These “rattled” structures allowed the optimizer to escape local minima and relax to a lower energy ground state structure. Such symmetry breaking has been shown to improve the optimization behavior in TiO 2 nanoparticles previously . As a general rule of thumb, it was suggested that structural perturbations of around −40% to +20% to provide optimal results …”
Section: Designing Robust Computational Modelsmentioning
confidence: 97%
“…Such symmetry breaking has been shown to improve the optimization behavior in TiO 2 nanoparticles previously. 32 As a general rule of thumb, it was suggested that structural perturbations of around −40% to +20% to provide optimal results. 29 In addition to random atomic perturbations, systematic modification of the starting geometry also has the potential to alter the optimization pathway.…”
Section: ■ Introductionmentioning
confidence: 99%